2015
DOI: 10.1016/j.reseneeco.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ willingness to pay for renewable energy: A meta-regression analysis

Abstract: JEL classification: C53 D62 Q40 Q48 Q51Keywords: Meta-regression Renewable energy Green electricity Valuation Willingness to pay a b s t r a c t Using renewable energy for domestic consumption has been identified as a key strategy by the Intergovernmental Panel on Climate Change to reduce greenhouse gas emissions. Critical to the success of this strategy is to know whether consumers are willing to pay to increase the proportion of electricity generated from renewable energy in their electricity portfolio. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 58 publications
6
64
1
Order By: Relevance
“…While a series of literature showed that education is an important indicator of willingness to pay higher prices and higher taxes for the protection of the environment (Bigerna and Polinori, 2014;Franzen and Vogl, 2013;Ivanova and Tranter, 2008;Kotchen et al, 2013;Zhang and Wu, 2012;Zorić and Hrovatin, 2012), some studies reported no significant or negative relationships between education and willingness to pay for the environment (Dorsch, 2011;Gökşen et al, 2002;Ma et al, 2015). Indeed, Adaman et al (2011) found it rather surprising that in Turkey individuals with university degree are not significantly more willing to pay for CO2 emission reductions from power production than those with no qualification.…”
Section: Willingness To Support For Environmental Taxmentioning
confidence: 99%
“…While a series of literature showed that education is an important indicator of willingness to pay higher prices and higher taxes for the protection of the environment (Bigerna and Polinori, 2014;Franzen and Vogl, 2013;Ivanova and Tranter, 2008;Kotchen et al, 2013;Zhang and Wu, 2012;Zorić and Hrovatin, 2012), some studies reported no significant or negative relationships between education and willingness to pay for the environment (Dorsch, 2011;Gökşen et al, 2002;Ma et al, 2015). Indeed, Adaman et al (2011) found it rather surprising that in Turkey individuals with university degree are not significantly more willing to pay for CO2 emission reductions from power production than those with no qualification.…”
Section: Willingness To Support For Environmental Taxmentioning
confidence: 99%
“…14 Meta-analyses have focused on the preference for hydropower (Mattmann 2016a), wind power (Mattmann et al 2016b), preferences for renewables in general (Sundt and Rehdanz 2015), preferences for several types of renewables in comparison with each other (Ma et al 2015), and preferences for several conventional and renewable technologies in comparison with each other (Sundquist 2004). Except for the latter article, they primarily refer to stated preference primary studies.…”
Section: Meta-analysesmentioning
confidence: 99%
“…(2) Comparative analysis Most scholars focus on the factors that affect the WTP for renewable energy [15,30], while we focus on the factors that influence residents' expectations of government subsidies for renewable energy. Uehleke [13] argued that gender had a significant impact on WTP; in our study, however, gender was found to have little effect on the results.…”
Section: Discussionmentioning
confidence: 99%